100. Sensory and autonomic small fiber involvement in CMT 1A. Issue 1 (January 2015) - Nolano, M.; Provitera, V.; Manganelli, F.; Pisciotta, C.; Iodice, R.; Stancanelli, A.; Saltalamacchia, A.M.; Lullo, F.; Caporaso, G.; Santoro, L.
<x xml:space="preserve">Abstract</x> Sensory symptoms in CMT1A are generally attributed to large fiber. However, an involvement of small fibers has been recently brought up. We performed an extensive clinical, morphological and functional study of cutaneous somatic and autonomic innervation in 10 patients affected by CMT 1A, in order to assess small fiber involvement in this condition. We used a 13 items questionnaire and QST to evaluate symptoms and function of somatic small fibers, DST, SSR and Ewing tests to evaluate autonomic function. Morphological analysis of cutaneous innervation included lENF density and sudomotor nerves assessment. Twenty age-and-sex-matched healthy subjects were used as controls for morphological data. All patients complained of at least 2 symptoms related to small fiber dysfunction. Nine out of ten patients had an increase in thermal/pain thresholds indicating an impairment of both C and A-delta fibers. DST revealed hypoidrosis in all patients (41.8 ± 22.8 vs 83.7 ± 17.3 sweat drops/cm2). SSR amplitude at feet was significantly lower (p < 0.05) in patients compared to controls (1.6 ± 0.7 versus 4.2 ± 3.2 mV). One patient showed a cardiac dysautonomia. Density of ENFs sudomotor nerves was significantly lower (p < 0.01) compared to age-and-sex-matched control subjects. Our findings confirm a sensory and autonomic small fiber damage in CMT 1A patients.